The Influence of Slang on Social Identity Formation among Teenagers in the Digital Era - Vika Fransisca; Aurelia Widya Astuti (PT Publikasiku Academic Solution, 2025)
This research examines the influence of slang on social identity formation among teenagers in the digital era. With the rise of digital communication platforms like Instagram, TikTok, and WhatsApp, slang has become an essential tool for teenagers to express themselves and navigate social relationships. This qualitative study combines semi-structured interviews and content analysis of social media interactions to investigate how teenagers use slang to construct their online identities. The findings reveal that slang is a crucial marker of group membership, reinforcing social bonds and facilitating resistance to societal norms. Teenagers associate their use of slang with belonging to specific peer groups and online subcultures. The study also highlights the role of digital spaces in shaping the evolution of slang and identity. The implications of these findings suggest that educators and parents should recognize the role of slang in adolescent development and digital communication. Future research should explore the cross-cultural variations of slang and its long-term impact on identity formation among teenagers.